2017
DOI: 10.17235/reed.2017.4449/2016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of esophageal motility in gastroesophageal reflux disease with and without globus sensation

Abstract: Globus GERD patients have a higher UES residual pressure, longer LES length, higher LES basal pressure and greater esophageal dysmotility than typical GERD patients. HRM is useful in evaluating esophageal motility of GERD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Studies focusing on UES motility in LPR patients are limited and controversial. A retrospective study that compared suspected LPR patients with typical GERD patients has revealed that LPR was characterized by higher UES residual pressure . Findings on UES motility were further supported by the efficacy of UES assist device in the patients with laryngeal symptoms .…”
Section: Discussionmentioning
confidence: 90%
“…Studies focusing on UES motility in LPR patients are limited and controversial. A retrospective study that compared suspected LPR patients with typical GERD patients has revealed that LPR was characterized by higher UES residual pressure . Findings on UES motility were further supported by the efficacy of UES assist device in the patients with laryngeal symptoms .…”
Section: Discussionmentioning
confidence: 90%
“…Esophageal motor abnormalities, particularly pertaining to the upper esophageal sphincter (UES) have been described in globus, but it remains unclear if the findings are causative of the symptom, or a consequence of concurrent anxiety. A reactive, hyperdynamic UES with respiration, 21 high UES resting pressures, 22 and elevated UES postswallow residual pressures 23,24 have been reported. There are limited data demonstrating that a lowering of UES pressure with neuromodulator therapy (paroxetine and amitriptyline) can be associated with improvement in globus symptoms 25 .…”
Section: Etiology Of Globusmentioning
confidence: 97%
“…104 Those globus patients who also have GORD may also have a longer UOS zone. 105 Repeated reactive dry swallowing and/or throat clearing might contribute to these observations, which may have a historical correlate in the so-called 'inferior constrictor strain swallow' described by Gray. 106 There is recent interest in ambulatory 24-hour oropharyngeal aerosol acid exposure assessment, which was used in 101 patients with GORD symptoms and cough, hoarseness, asthma symptoms or globus sensation alongside concomitant oesophageal pH monitoring.…”
Section: Update On Ph-metry and Manometry In Throat Symptomsmentioning
confidence: 99%